TRANSFER PRICING PADA ADARO ENERGY: PENDEKATAN ANALISIS FUNGSIONAL - Wibowo, Nicholas Jonathan Hendrik (Widya Mandala Surabaya Catholic University, 2021)
This research examines the funtional analysis in the case of Adaro Indonesia and Coaltrade as reported by Global Witness in order to explain the practicality of functional analysis and its relation to the fairness aspect of transfer pricing. This research was perpetrated using a descriptive qualitative method and utilised secondary data obtained from Global Witness’ report and combined with other data from Adaro Energy’s annual report in order to reduce bias in the analysis. In making the analysis, this research used secondary data analysis strategy and grounded theory approach in order to make a valid reasoning. In practice, functional analysis involved some process and identification including identification of entity involved, identification of perspective in the analysis, identification of relevant business process in terms of asset usage and business risk, and the classification of business models. The results show that the transfer pricing scheme in which Coaltrade served as full risk distributor indicated unfairness in the compensation since Coaltrade was able to earn more profit than Adaro Indonesia despite the low risk nature of the business. In that sense, functional analysis is related to the fairness aspect of transfer pricing in some way in regards that functional analysis enables analyst to get the big picture on the compensation earned by each entity invovled. An indication of unfair transfer pricing and tax evasion may arise in the case that a lower risk entity earns more than the higher risk one.